Evaluation of the Biodistribution of Mesenchymal Stem Cells in a Pre-clinical Renal Tuberculosis Model by Non-linear Magnetic Response Measurements - Yudintceva, Natalia; Mikhailova, Natalia; Bobkov, Danila; Yakovleva, Liudmila; Nikolaev, Boris; Krasavina, Darya; Muraviov, Alexandr; Vinogradova, Tatiana; Yablonskiy, Petr; Samusenko, Igor; Ryzhov, Vyacheslav; Deriglazov, Vladimir; et al. (Frontiers in Physics, 2021)
Bone-marrow derived mesenchymal stem cells (MSCs) exert anti-tuberculosis effects due to their potential to repair damaged tissues and modulate inflammatory immune responses. MSCs were reported to be recruited to the Mycobacterium tuberculosis (Mtb) affected sites in the organism. However, due to limitations of presently applied in vivo imaging techniques the trafficking and biodistribution of MSCs in Mtb-infected organisms is not possible. In the current study MSCs were labeled with superparamagnetic iron oxide nanoparticles (SPIONs) as a negative MR contrast agent for imaging of the biodistribution of MSCs in vivo. Trafficking of SPIONs-labeled MSCs was analyzed in a preclinical model of renal tuberculosis in male Chinchilla rabbits (n = 18) following intravenous administration on days 0, 2, 3, and 7 employing highly sensitive method of nonlinear longitudinal magnetic response (NLR-M2) measurements. Within 48 hours after injection nanoparticles-labeled MSCs accumulated predominantly in lung, spleen, liver tissues, and paratracheal lymph nodes with a subsequent decrease over the observation period of 7 days. The recruitment of MSCs to Mtb-affected organs was further proven by immunohistological analysis. The highly sensitive method of NLR-M2 allowed the detection of SPIONs-labeled cells at low concentrations in different organs and tissues giving insights of in vivo mesenchymal stem cells trafficking in organism after TB infection.